Biosynthesis of ZnO Nanoparticles using Lime Leaf Extract (Citrus auraantifolia) for Identification of Latent Fingerprints - Sri Adelila Sari; Dinda Hawari (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
Fingerprints are an identification tool in forensic science because of their unique properties. Unfortunately, some of the chemicals used in fingerprint powders are toxic and pose a potential health hazard. This study was conducted to analyze the ability of ZnO nanoparticles to identify latent fingerprints. ZnO nanopowder was synthesized with lime leaf extract using the green synthesis method with double-distilled water solvent and characterized by FT-IR at a wavenumber of 4000-400 cm-1 and SEM-EDX analysis to provide information about the morphology and to detect the elemental composition nanoparticles. The average particle diameter through SEM was around 173.4 nm and formed a spherical with a rough surface with beige color. Identification of latent fingerprints using the powder dusting method on various porous surfaces (craft paper and greaseproof paper) and non-porous surfaces (glass preparations, aluminium foil, and compact disk) shows visualization with the characteristics of the ridges that look good and clear. The study showed the highest frequency of loops (47%), followed by double loops (20%), plain whorls (30%), and central pocket whorls pattern (3%) from 30 fingerprint samples consisting of 14 men and 16 women. Development identification fingerprints using TiO2 show visualization more clearly because color contrast from bright white color and detail ridges is shown better with ZnO nanopowder.